Characterizing and Optimizing Piezoelectric Response of ZnO Nanowire/PMMA Composite-Based Sensor - Zhang, Xiaoting (Nanomaterials (Basel), 2021)
Due to the outstanding coupling between piezoelectric and semiconducting properties of zinc oxide nanowires, ZnO NW-based structures have been demonstrating promising potential with respect to their applicability in piezoelectric, piezotronic and piezo-phototronic devices. Particularly considering their biocompatibility and biosafety for applications regarding implantable medical detection, this paper proposed a new concept of piezoelectric composite, i.e., one consisting of vertically aligned ZnO NW arrays and an insulating polymer matrix. First, the finite element method (FEM) was employed to drive optimization strategies through adjustment of the key parameters such as Young’s modules and the dielectric constant of the dielectric constituents, together with the density and dimension of nanowire (NW) itself. Second, to investigate the functionality of each individual layer of composite, different designed structures were fabricated and characterized in terms of electrical and piezoelectric properties. Next, experimental and simulation tests were performed, indicating that the decreasing thickness of the top poly(methyl methacrylate) layer (PMMA) can substantially enhance the piezoelectric sensitivity of the ZnO NW composite. Besides the further benefit of no polarization being needed, our material has a comparable charge coefficient (d(33)) with respect to other lead-free alternatives (e.g., BaTiO(3)), confirming the high sensing abilities of the developed structure based on vertically aligned ZnO NW arrays. Finally, a time-varying model combining piezoelectricity and electric circuit modules was investigated in detail, giving rise to an estimation of the d(33) coefficient for ZnO NWs. Based on this study, the developed material is revealed to be highly promising in medical applications, particularly regarding the FFR technique, where coronary pressure can be measured through a piezoelectric sensor.